Factors affecting the United Nations' response to natural disasters: what determines the allocation of the Central Emergency Response Fund?. Issue 4 (30th January 2017) - Robinson, Tyler D.; Oliveira, Thiago M.; Kayden, Stephanie
Abstract : Natural disasters can overwhelm the domestic response of a country, leaving it dependent on external humanitarian relief. The Central Emergency Response Fund (CERF) of the United Nations centralises humanitarian funding and thus allows for a rapid response. This study combined data to analyse the factors that affected the allocation of CERF funding to countries that suffered a natural disaster between 2007 and 2013. It generated descriptive statistics and information on relative risks, and performed regressions of CERF funding across countries. There were 4, 346 disasters in total in 188 countries between 2007 and 2013. CERF provided USD 2.98 billion to 87 countries, comprising 3.3 per cent of their total humanitarian funding. CERF more frequently supplied aid to countries in North Africa and the Middle East, and to those that had suffered geophysical disasters. Appropriately, it funds vulnerable countries experiencing severe natural disasters, yet its funding may be affected by variables beyond severity and vulnerability. Further investigation is warranted, therefore.